Uncommon Alliances: Cultural Narratives of Migration in the New Europe - Kovacevic, Natasa (Edinburgh University Press, 2018)
Uncommon Alliances: Cultural Narratives of Migration in the New Europe takes a critical stance toward both assimilationist and multicultural imaginings of community in the European Union that occlude neocolonial relations of dependence and exclusion.